Migration of foreign bodies through the urinary system (clinical cases) - O. A. Baulina; A. A. Baulin; V. A. Baulin; L. A. Aver'yanova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Introduction. Migration of implantable materials is a rare but significant complication of surgical interventions in urological practice. Objective: to present an analysis of two clinical cases of unusual migration of fixing Capron (nylon) structures in the urinary system. Materials and methods. Two clinical observations are described: a case of migration of a fixing Capron suture into the kidney parenchyma after nephropexy and a case of transurethral migration of a supporting loop after surgery for urinary incontinence. Diagnostics was carried out using clinical examination, ultrasound imaging, computed tomography, and endoscopic methods. Results. In the first case, the migration of the Capron suture into the kidney parenchyma was successfully resolved through laparoscopic removal of the structure and replacement with a polypropylene one. In the second case, spontaneous transurethral migration of the fixing loop occurred without the development of stricture and with preservation of the functional result of the operation. Conclusion. The presented observations demonstrate the possibility of gradual migration of Capron structures through the tissues of the urinary system without developing serious complications. These cases emphasize the importance of suture material selection in urological operations and the need for long-term patient monitoring.